The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1126/science.aav6618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preexisting dengue immunity on Zika virus emergence in a dengue endemic region

Abstract: The clinical outcomes associated with Zika virus (ZIKV) in the Americas have been well documented, but other aspects of the pandemic, such as attack rates and risk factors, are poorly understood. We prospectively followed a cohort of 1453 urban residents in Salvador, Brazil, and, using an assay that measured immunoglobulin G3 (IgG3) responses against ZIKV NS1 antigen, we estimated that 73% of individuals were infected during the 2015 outbreak. Attack rates were spatially heterogeneous, varying by a factor of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
212
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(242 citation statements)
references
References 43 publications
19
212
2
2
Order By: Relevance
“…An in vitro study showed enhancement of ZIKV replication in the presence of DENV antibodies (23). However, clinical cohort and case control studies of individuals in dengue endemic regions suggest the opposite, that pre-existing dengue immunity reduces the risk of symptomatic ZIKV infection and congenital ZIKV syndrome (13, 14, 26). Pantoja et al .…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study showed enhancement of ZIKV replication in the presence of DENV antibodies (23). However, clinical cohort and case control studies of individuals in dengue endemic regions suggest the opposite, that pre-existing dengue immunity reduces the risk of symptomatic ZIKV infection and congenital ZIKV syndrome (13, 14, 26). Pantoja et al .…”
Section: Discussionmentioning
confidence: 99%
“…Differences were also observed in B-cells and T-cells activation and cytokines and chemokines profile (24). Our previous results have been recently validated in a metanalysis using most of the NHP available data (32) and more relevant, in two studies presenting real settings of humans living in DENV-endemic areas (32-34). In this work, we aimed to establish the contribution of different DENV convalescent periods (3 months or early and 12 months or middle convalescent periods) on the immune response and disease course after ZIKV infection.…”
Section: Discussionmentioning
confidence: 61%
“…However, playing a significant role controlling ZIKV viremia and liver damage happens only after a middle-convalescent period of approximately 12 months, but not too early (3 months) or too late (2.8 years) after the primary DENV infection. Interestingly a recent report showed that the IgG3 levels (a marker of recent DENV infection) were positively associated with risk of infection by ZIKV (34). In humans, this fact correlates with our finding in NHPs that a shorter period of DENV immunity may not provide same level of protection against ZIKV replication.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with in vitro and murine studies that have shown significant enhancement of secondary ZIKV infection in the presence of anti-flavivirus antibodies (12, 15, 53, 54). Whether this is consistent with secondary ZIKV infections in humans is unknown, but recent human cohort studies suggest more similarities with macaques (5, 21, 22, 54). In addition, there was, at most, a minimal difference in peak DENV vRNA load between animals with and without prior ZIKV exposure, suggesting that prior ZIKV exposure may only minimally affect DENV disease, at least in macaques.…”
Section: Discussionmentioning
confidence: 74%